Stillbirth and fetal anomalies: secondary analysis of a case–control study. (14th October 2020) - Son, SL; Allshouse, AA; Page, JM; Debbink, MP; Pinar, H; Reddy, U; Gibbins, KJ; Stoll, BJ; Parker, CB; Dudley, DJ; Varner, MW; Silver, RM
Abstract : Objective: Approximately 10% of stillbirths are attributed to fetal anomalies, but anomalies are also common in live births. We aimed to assess the relationship between anomalies, by system and stillbirth. Design: Secondary analysis of a prospective, case–control study. Setting: Multicentre, 59 hospitals in five regional catchment areas in the USA. Population or sample: All stillbirths and representative live birth controls. Methods: Standardised postmortem examinations performed in stillbirths, medical record abstraction for stillbirths and live births. Main outcome measures: Incidence of major anomalies, by type, compared between stillbirths and live births with univariable and multivariable analyses using weighted analysis to account for study design and differential consent. Results: Of 465 singleton stillbirths included, 23.4% had one or more major anomalies compared with 4.3% of 1871 live births. Having an anomaly increased the odds of stillbirth; an increasing number of anomalies was more highly associated with stillbirth. Regardless of organ system affected, the presence of an anomaly increased the odds of stillbirth. These relationships remained significant if stillbirths with known genetic abnormalities were excluded. After multivariable analyses, the adjusted odds ratio (aOR) of stillbirth for any anomaly was 4.33 (95% CI 2.80–6.70) and the systems most strongly associated with stillbirth were cystic hygroma (aOR 29.97, 95% CI 5.85–153.57), and thoracic (aOR16.18, 95% CI 4.30–60.94) and craniofacial (aOR 35.25, 95% CI 9.22–134.68) systems. Conclusions: In pregnancies affected by anomalies, the odds of stillbirth are higher with increasing numbers of anomalies. Anomalies of nearly any organ system increased the odds of stillbirth even when adjusting for gestational age and maternal race. Tweetable abstract: Stillbirth risk increases with anomalies of nearly any organ system and with number of anomalies seen. Tweetable abstract: Stillbirth risk increases with anomalies of nearly any organ system and with number of anomalies seen.